A high-performance operational amplifier for infrared readout circuit application. Issue 6 (March 2019) - Zhou, Tong; Liu, Han; Xu, Yun; Jiang, Bo; Su, Yan
Abstract: The infrared readout circuit is a highly integrated circuit that integrates various functions into a single semiconductor chip. As the important part of readout circuit, the operational amplifier (OPA) decides the performance of the readout circuit. This paper describes a kind of OPA, which is used in infrared focal plane array (IRFPA) readout circuit structure based on the capacitive trans-impedance amplifier (CTIA) including the analysis and design of the OPA. Spectra is employed to simulate the circuit and obtain the results which is according with the designed objectives. The open-loop gain reaches 101 dB and the phase margin is 87°with the ICMR (input common-mode range) ranging from 201.6 mV to 4.01 V．